Risk factors for myocardial dysfunction after traumatic brain injury: A one-year follow-up study. Issue 8 (August 2017) - Lu, Kang; Liang, Cheng-Loong; Li, Ping-Chia; Liliang, Po-Chou; Huang, Chih-Yuan; Lee, Yi-Che; Wang, Kuo-Wei; Yang, San-Nan; Sun, Yuan-Ting; Wang, Hao-kuang
Abstract: Introduction: Traumatic brain injury has been associated with an increased risk of myocardial dysfunction. Common abnormalities accompanying this pathology include electrocardiographic abnormalities, elevated creatine kinase levels, arrhythmias, and pathologic changes of the myocardium. The aim of this study was to determine if TBI patients have a higher risk of myocardial dysfunction than the general population and to identify the risk factors of myocardial dysfunction in TBI patients. Patients and methods: The study sample was drawn from Taiwan's National Health Insurance Research Database of reimbursement claims, and comprised 26, 860 patients who visited ambulatory care centers or were hospitalized with a diagnosis of TBI. The comparison group consisted of 134, 300 randomly selected individuals. The stratified Fine and Gray regression was performed to evaluate independent risk factors for myocardial dysfunction in all patients and to identify risk factors in TBI patients. Results: During a 1-year follow-up period, 664 patients with TBI and 1494 controls developed myocardial dysfunction. TBI was independently associated with increased risk of myocardial dysfunction. Diabetes, hypertension, peptic ulcer disease, chronic liver disease and chronic renal disease were risk factors of myocardial dysfunction in TBI patients. Conclusions: Individuals with TBI are at greater risk of developing myocardial dysfunction after adjustments for possible confounding factors. Early monitor should be initiated to decrease disability and dependence in patients with TBI.